Prevalence of non‐steroidal anti‐inflammatory drugs (NSAIDs) use in patients with hypertensive crisis. Issue 1 (12th January 2022) - Jahangiri, Soodeh; Mousavi, Seyed Hamidreza; Hatamnejad, Mohammad Reza; Salimi, Maryam; Bazrafshan, Hamed
Abstract: Backgound: One of the known risk factors for hypertensive crisis (HTN‐C) is non‐steroidal anti‐inflammatory drugs (NSAIDs) which their adverse effects can lead to end‐organ damage such as gastrointestinal and cardiovascular issues. Aims: Data on the correlation between NSAIDs and HTN‐C are limited. In this study, we determined the prevalence of NSAID use among patients with HTN‐C. Materials & Methods: This cross‐sectional study was conducted among patients primarily diagnosed with HTN‐C referred to Alzahra hospital, Shiraz, Iran from April 2015 to April 2020. Demographic data, as well as information regarding the past medical and drug history and laboratory findings, were gathered retrospectively. The history of NSAID use was also asked specifically. The collected data were analyzed by SPSS and the P ‐value less than .05 was considered significant. Results: A total of 257 patients with a mean age of 59.73 were enrolled in the study. Among them 62.6% were female and 137 patients (53.33%) used NSAIDs. Of all the patients 197 (76.7%), 71 (27.6%), and 46 (17.9%) suffered from concomitant hypertension (HTN), diabetes mellitus (DM), and ischemic heart disease (IHD) respectively. A significant relation was found between having each of the comorbidities and NSAIDs use among HTN‐C patients ( P ‐value <.0001). NSAIDs use was also significantly higher in older age ( P ‐value <.0001) and female gender ( P ‐value <.02). A high rate of NSAID use was seen among HTN‐C patients with a positive significant correlation to concomitant diseases, older age, and female gender. Conclusion: The Results of our study indicate that NSAIDs are frequently used among those with HTN‐C and considering the adverse effects of these medication our results further highlight the importance of monitoring and limiting NSAID use.